2022
DOI: 10.48550/arxiv.2207.12408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Possibility of Additional Intergalactic and Cosmological Dark Matter

Abstract: The entropies of the known entities in the universe add to a total which is some twenty orders of magnitude below the holographic limit. Based on an assumption that the entropies should saturate the limit, we suggest that there exists dark matter, in the form of extremely massive primordial black holes, in addition to the dark matter known to exist inside galaxies and clusters of galaxies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Assuming that primordial extremely massive black holes (PEMBHs) of masses in the range of 10 12 to 10 14 solar masses actually exist, as put forward in [10,11], and [12], we explored the possible effects of these extremely massive primordial black holes carrying the extreme charges as discussed in [9], which are based on a linear extrapolation of the relations set up in [3]. The latter extrapolation causes these charged primordial extremely massive black holes (CPEMBHs) to become naked singularities, if they can be described as Reissner-Nordström black holes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that primordial extremely massive black holes (PEMBHs) of masses in the range of 10 12 to 10 14 solar masses actually exist, as put forward in [10,11], and [12], we explored the possible effects of these extremely massive primordial black holes carrying the extreme charges as discussed in [9], which are based on a linear extrapolation of the relations set up in [3]. The latter extrapolation causes these charged primordial extremely massive black holes (CPEMBHs) to become naked singularities, if they can be described as Reissner-Nordström black holes.…”
Section: Discussionmentioning
confidence: 99%
“…Primordial black holes (PBHs) have long been established as dark matter candidates, [15,31], and signatures are being searched for on mass scales ranging from sub-solar masses to primordial supermassive black holes (PSBHs) with up to 10 11 solar masses, M , see, for instance, [6,7] or [27] for recent overviews. To extend the mass range to higher masses, [10,11] introduced primordial extremely massive black holes (PEMBHs) with masses between 10 11 and 10 22 M and showed that they are necessary to saturate the holographic entropy bound of the visible universe. The latter can be considered the entropic analogue of the cosmic critical mass density.…”
Section: Introductionmentioning
confidence: 99%